Employing websites in language learning for tourism purpose among Arabic learners at the MARA Poly-Tech College (KPTM) - Abdul Ghani, Mohammad Taufiq; Wan Daud, Wan Ab Aziz; Sahrir, Muhammad Sabri (Springer, 2016)
This paper examines the effectiveness of using websites in learning Arabic language for tourism purposes at the Department of General Studies, MARA Poly-Tech College (KPTM), Kelantan Darul Naim, Malaysia. This descriptive study sheds light on the issues in learning Arabic for specific purposes and analyzes the effectiveness of employing websites as the main tool in learning activities. This data was collected through a questionnaire survey and observation of the Basic Arabic Course for Tourism and Hospitality (HFA-1023) among 43 students who have registered and undergone the course for one semester in 2015. Descriptive quantitative analysis was used to analyze the data by using IBM SPSS statistical software. In general, the findings show that the use of a websites in learning the Arabic language for the purpose of tourism is effective among learners, and it provides good and proactive support for students in learning a language for specific purposes.